The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jneuroim.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced costimulation by CD70+ B cells aggravates experimental autoimmune encephalomyelitis in autoimmune mice

Abstract: Expression of CD70 by B cells aggravates EAE possibly by reducing the number of regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…Interestingly, anti-CD70 antibody-mediated blocking of CD70 prevented EAE in SJL/J mice (121), and over-expression of CD70 on the B cells enhanced EAE (126). This is in contrast to what is reported by Coquet et al (124).…”
Section: Cd70-cd27mentioning
confidence: 59%
See 3 more Smart Citations
“…Interestingly, anti-CD70 antibody-mediated blocking of CD70 prevented EAE in SJL/J mice (121), and over-expression of CD70 on the B cells enhanced EAE (126). This is in contrast to what is reported by Coquet et al (124).…”
Section: Cd70-cd27mentioning
confidence: 59%
“…Differential entry sites into the CNS likely contribute to location specificity. Expression of CCL20 (a CCR6 ligand) by epithelial cells of the choroid plexus appear to promote CCR6-regulated entry of Th17 cells (126). Whether anatomical differences in the tissue structure or ECM composition at these locations impacts the efficiency of Th1 or Th17 migration is not yet clear.…”
Section: Unique Lanscape Of the Cnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coquet et al [20] found that the CD27-CD70 costimulatory pathway impeded Th17 cell differentiation and associated autoimmunity in experimental autoimmune encephalomyelitis (EAE) by selectively repressing the transcription of IL-17 and CCR6 [21]. However, other studies found that CD27-CD70 signal-blocking prevented EAE in SJL/J mice [22] and the overexpression of CD70 in B cells enhanced EAE in 2D2 mice [23]. Although the role of CD27-CD70 in Th17 regulation is inconsistent, maybe due to the pleiotropic and complex effects of CD70-CD27 interaction on T cell and B cell activation [9, 10], CD27-CD70 is sure to be one of the components of the Th17 pathway.…”
Section: Discussionmentioning
confidence: 99%